2018
DOI: 10.3390/ijms19041086
|View full text |Cite
|
Sign up to set email alerts
|

Correcting Calcium Dysregulation in Chronic Heart Failure Using SERCA2a Gene Therapy

Abstract: Chronic heart failure (CHF) is a major contributor to cardiovascular disease and is the leading cause of hospitalization for those over the age of 65, which is estimated to account for close to seventy billion dollars in healthcare costs by 2030 in the US alone. The successful therapies for preventing and reversing CHF progression are urgently required. One strategy under active investigation is to restore dysregulated myocardial calcium (Ca2+), a hallmark of CHF. It is well established that intracellular Ca2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 71 publications
(99 reference statements)
0
20
0
3
Order By: Relevance
“…SERCA2a is responsible for pumping calcium back to the SR during diastole to avoid an increase in intracytoplasmic calcium concentration, which may increase the sodium-calcium exchange and triggered activity. PLB has been demonstrated to bind to SERCA2a and inhibit its activity; following phosphorylation, this inhibition of SERCA2a is lost (17). In the present study, SECA2a and P-PLB expression was impaired during Nkx2.5 silencing.…”
Section: Discussionmentioning
confidence: 99%
“…SERCA2a is responsible for pumping calcium back to the SR during diastole to avoid an increase in intracytoplasmic calcium concentration, which may increase the sodium-calcium exchange and triggered activity. PLB has been demonstrated to bind to SERCA2a and inhibit its activity; following phosphorylation, this inhibition of SERCA2a is lost (17). In the present study, SECA2a and P-PLB expression was impaired during Nkx2.5 silencing.…”
Section: Discussionmentioning
confidence: 99%
“…TH also positively regulates sarcoplasmic reticulum Ca 2+ ATPase ( Serca2a ) gene expression 69 , 76 , 77 ( Figure 3 ). Serca2a is an important Ca 2+ pump for the maintenance of Ca 2+ homeostasis, which is associated with myocardial calcium handling and plays a critical role in maintaining cardiac function 78 , 79 .…”
Section: Pathophysiological Role Of Med13 In the Heartmentioning
confidence: 99%
“…The results of the initial Phase I and IIa trials suggested that AAV1.SERCA2a treatment reduced the number of cardiac events in HF patients ( Jaski et al, 2009 ; Jessup et al, 2011 ); however, larger Phase IIb clinical trials failed to show improvement in any primary or secondary endpoints, leading to their early termination ( Hulot et al, 2017 ). The failure of these clinical trials suggests the dosage and delivery method of AAV1.SERCA2a may require optimizing ( Hulot et al, 2016 ) [SERCA2a gene therapy in HF has been extensively reviewed elsewhere ( Samuel et al, 2018 )]. Despite the lack of promising results for AAV1.SERCA2a, clinical trials are underway for istaroxime, a dual functional luso-inotropic agent which both stimulates SERCA2a and inhibits Na + /K + ATPase ( Micheletti et al, 2002 ) ( Figure 4 and Table 2 ).…”
Section: Calcium Handling Proteins In Cardiac Hypertrophy and Hf And mentioning
confidence: 99%